Trajnostna destinacijska komunikacija v teoriji in praksi - Hazemali, David; Onič, Tomaž; Mohar, Tjaša; Majcenovič Kline, Barbara; Prajnč Kacijan, Nastja; Plemenitaš, Katja; Hempkin, Kirsten; Vovk, Ana; Leva, Bernarda (Komuniciranje okoljske krize, 2025)
The article explores the concept of sustainable destination communication as a vital pillar of contemporary tourism development. It highlights the central role of communication in promoting sustainable behaviour, building trust, and fostering long-term relationships between destinations, visitors, and local communities. The authors argue that merely using the term sustainability is insufficient – communication must be credible, strategic, and inclusive. The paper presents ten principles of effective sustainability communication, developed by Baumgartner and Hadorn (2022), and illustrates their application through a case study of the Green Planica 2023 Sustainability Initiative. This initiative, created for the Nordic World Ski Championships in Slovenia, demonstrates how even large-scale events can successfully embody sustainability values through well-designed communication. The study concludes that sustainable communication is not just a promotional tool but a transformative process essential for creating responsible, inclusive and resilient tourism destinations.